2006
DOI: 10.1074/jbc.m602033200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Interaction of the Plasma Membrane Na+/Ca2+ Exchangers with the 14-3-3 Proteins

Abstract: The three Na ؉ /Ca 2؉ exchanger isoforms, NCX1, NCX2, and NCX3, contain a large cytoplasmic loop that is responsible for the regulation of activity. We have used 347 residues of the loop of NCX2 as the bait in a yeast two-hybrid approach to identify proteins that could interact with the exchanger and regulate its activity. Screening of a human brain cDNA library identified the ⑀ and isoforms of the 14-3-3 protein family as interacting partners of the exchanger. The interaction was confirmed by immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The large cytosolic loop interacts with several proteins: the 14-3-3 protein, phosphorylated PLM ( phospholemman, a member of a family of transport regulators, best known as modulators of Na, K-ATPase activity) and calcineurin: they all have inhibitory function on NCX activity (Katanosaka et al 2005;Pulina et al 2006;Wang et al 2006;Zhang et al 2006). Other proteins have also been shown to interact with the NCX: ankyrin (Li et al 1993), the filamentous actin network (Condrescu and Reeves 2006), caveolin 3 (in the heart) (Bossuyt et al 2002;Camors et al 2006), and caveolin 1 and 2 (in neuronal cells) (Cha et al 2004).…”
Section: Sodium/calcium Exchanger Structural and Regulatory Charactermentioning
confidence: 99%
“…The large cytosolic loop interacts with several proteins: the 14-3-3 protein, phosphorylated PLM ( phospholemman, a member of a family of transport regulators, best known as modulators of Na, K-ATPase activity) and calcineurin: they all have inhibitory function on NCX activity (Katanosaka et al 2005;Pulina et al 2006;Wang et al 2006;Zhang et al 2006). Other proteins have also been shown to interact with the NCX: ankyrin (Li et al 1993), the filamentous actin network (Condrescu and Reeves 2006), caveolin 3 (in the heart) (Bossuyt et al 2002;Camors et al 2006), and caveolin 1 and 2 (in neuronal cells) (Cha et al 2004).…”
Section: Sodium/calcium Exchanger Structural and Regulatory Charactermentioning
confidence: 99%
“…It has been shown that 14-3-3 protein interacts with the three NCX isoforms and inhibits NCX activity (15). In smooth muscle cells, NCX co-localizes with Na ϩ /K ϩ -ATPase in regions closed to the sarcoplasmic reticulum that store Ca 2ϩ , which suggests a connection between NCX with its associated Na ϩ /K ϩ -ATPase and Ca 2ϩ release from the sarcoplasmic reticulum (16).…”
mentioning
confidence: 99%
“…An inhibitory effect of 14-3-3ε was also observed on NCX (24) and Ca 2ϩ -ATPase (25). However, the mechanism underlying the negative regulation by 14-3-3 is unknown.…”
Section: F76mentioning
confidence: 91%
“…Some membrane proteins can interact with multiple 14-3-3 isoforms. For example, NCX2 interacts with 14-3-3 ␤-, -, -, and ε-isoforms (24). At least three isoforms of 14-3-3 (, , and ) have been reported to interact with the cardiac voltage-gated Na ϩ channel Nav1.5 (1).…”
Section: F75mentioning
confidence: 99%
See 1 more Smart Citation